RELATIONSHIP BETWEEN OVERWEIGHT AND OBESITY WITH LOWER URINARY TRACT SYMPTOMS (LUTS) DUE TO BENIGN PROSTATIC HYPERLASIA IN PRE-ELDERLY A PRELIMINARY STUDY - Rusli, Bryant Agustino; Prihadi, Johannes Cansius; Rensa; Laurentius Aswin Pramono (Indonesian Urological Association, 2023)
ABSTRACT Objective: The purpose of this study is to find the relation between overweight and obesity with lower urinary tract symptoms due to benign prostatic hyperplasia in pre-elderly. Material & Methods: This analytical study was conducted in a cross sectional manner to 113 respondents. LUTS assessment uses the International Prostate Symptoms Score questionnaire. Measurements for overweight and obesity, this study uses the BMI and waist circumference methods. Fisher's exact test with SPSS v.25 was used for data analysis. Results: Results from data analysis showed that there was no significant relationship between overweight and obesity based on the BMI method on LUTS, p = 0.122. The results also showed a significant relationship between central obesity and LUTS, p = 0.003. Conclusion: Central obesity can be identified as a risk factor for LUTS while overweight and obesity based on the BMI method cannot be considered as a risk factor. These results can be used as education for pre-elderly to reduce the risk of LUTS due to BPH. Keywords: Overweight, obesity, lower urinary tract symptoms, benign prostatic hyperplasia, pre-elderly.